(untitled) (Journal of Invasive and Clinical Cardiology, 2025)
In our day-to-day practical settings of percutaneous coronary intervention (PCI), we sometimes encounter difficulty in introducing a guidewire (GW) to the markedly angulated side branch (SB), and the reverse wire technique is considered as a last resort to overcome such a situation. It involves the use of a guidewire with a hairpin curve, which is delivered beyond bifurcation alone. The RWT was first reported in 2008 and has since been improved with the support of a dual lumen microcatheter (DLC), making it a common technique among PCI operators.1 The first step of this technique involves the delivery of the reverse wire system to the target bifurcation. It’s important to note that this technique requires careful consideration of the anatomic features of the bifurcation and the lesion’s characteristics.2 Angiographic predictors of difficult side branch wiring (Figure 1) are severe calcifications involving the proximal main vessel and/or ostial side branch; severe stenosis with a large plaque burden in the proximal main vessel; tortuosity in the proximal main vessel limiting guidewire manipulations, and consequently access to the side branch as well as severe stenosis at the side branch ostium; and flow less than TIMI 3 in the side branch. Steps of Reverse Wire Technique (RWT)3: Here are the steps involved in performing the RWT: 1. Delivery of the Reverse Wire System: The first step involves delivering the reverse wire (RW) system, which consists of a hairpin-shaped guidewire and a dual-lumen microcatheter (DLC), to the targeted bifurcation 2. Reverse Wiring of the Side Branch: After advancing the RW system beyond the bifurcation, the DLC is pulled back proximally 3. Considerations and Tips: The RWT is particularly useful when regular wiring techniques fail to access in extremely angulated side branches. We should remember that the RWT should be considered as a last resort when other strategies fail to access extremely angulated side branches. Despite the potential complications, it remains a valuable tool in overcoming challenging anatomical scenarios during coronary interventions. J Inv Clin Cardiol 2024; 6(1): 25-28